Математичне узагальнення результатів експериментів зі спостереження розвитку одиничних двійникових прошарків у металевих матеріалах - Bosin, M.E.; Drygach, T.G.; Russkin, V.M. (Publishing house "Academperiodika", 2021)
A mathematical model has been proposed for the development of single twin layers in metal crystals under various loading regimes and various conditions. The model parameters depend on the geometric characteristics of the twin layer, the physical characteristics of the crystal, the Burgers vector, and the motion velocity of twin dislocations. Methods for the determination of the phenomenological parameters from experimental data were developed. In some cases, a comparison of the parameter values calculated in the framework of the proposed mathematical model with those obtained from experimental data was made, which demonstrated their satisfactory consistency. The proposed model can be useful for the development of a quantitative theory of twinning.